Dynamic Metal–Ligand Interaction of Synergistic Polymers for Bistable See‐Through Electrochromic Devices. Issue 8 (17th January 2022) - Wang, Yuyang; Shen, Ruipeng; Wang, Shuo; Zhang, Yu‐Mo; Zhang, Sean Xiao‐An
Abstract: Bistable electrochromic materials are a promising alternative solution to reduce energy consumption in displays. Limited by the mechanism and lack of a design strategy, only a few electrochromic materials have truly been able achieve bistability. Herein, a novel strategy is proposed to design bistable electrochromic materials based on polymer‐assisted dynamic metal–ligand coordination. The mechanism and materials of such unconventional electrochromic systems are proved by sufficient characterization. Synergistic stabilization of polymerized switchable dyes and the ionic ligand polymer are attracted to each other by supramolecular forces. The color states of the dye molecules are controlled and stabilized by valence changes of the metal ions. Meanwhile, through the polymerization of the electrochromic material and the nearby metal–ligand material, the metal ions of the electroinduced valence change are tightly fixed, and the related diffusion problem of the active EC component is also almost completely suppressed. This strategy successfully enables preparation of the corresponding transparent electrochromic displays with good performances, such as, the display information is clearly visible for more than 1.5 h without consuming energy. Furthermore, the new way of dynamic coordination or dissociation bistable displays could likely prosper the development of the electrochromic area and inspire other fields. Abstract : A flexible see‐through bistable electrochromic display based on polymer‐assisted dynamic metal–ligand coordination is achieved successfully. It benefits from the stabilization of dye molecules by metal ions, the fixing effect, and the inhibited diffusion for metal ions by the closely associated ligand polymers. The synergistic polymers possess good film‐forming ability, easy fabrication, and high transmittance with excellent bistability. These contribute potential for energy‐saving displays.